6 - Os Mídia e os Direitos Humanos na Guiné-Bissau : o caso dos jornais Nô Pintcha, Diário de Bissau e Gazeta de Notícias - Miguel de Barros, (Africa Media Review, 2012)
This article is part of the project Media and Human Rights in the Lusophone area, funded by CODESRIA. It seeks to identify, understand and explain the dynamics of newspapers addressing human rights in Guinea-Bissau. Referring to political liberalization (1991) which led to the liberalization of the media, the emergence of private investment, and the end of the political-military conflict (1999) until today, marked by complicated relationships between journalists and the power and the Guinean pressures perpetrated by security agents against opposition political leaders, human rights defenders and journalists. Thus, the effectiveness of freedom of the press was weakened by the lack of an institutional environment, economic and social environment favorable to their rigorous exercise. Notwithstanding this, the activity of the media has contributed to the consolidation of democracy and developed a spirit of citizenship.